2006
DOI: 10.1007/s00277-005-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E but not bcl-2, bax or mcl-1 is differentially expressed in ZAP 70-positive and ZAP 70-negative B-CLL cells

Abstract: The clinical course of chronic lymphocytic leukemia is variable. While some patients have indolent disease, others require aggressive treatment within a short time after diagnosis. Differences in the expression of proteins regulating cell cycle and apoptosis may be responsible for the heterogeneous course of the disease. Recently, protein ZAP 70 [zeta-chain (T-cell receptor) associated protein kinase 70 kDa] has been found to be differentially expressed within two biologic subgroups, characterized by the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Moreover, we found that bcl2-CD71-subset was significantly correlated with lower ZAP-70 (p ¼ 0.001), thus hypothesizing a reduced proliferation and higher apoptosis within ZAP-70 negative CLL subset. On this line, Bogner et al [46] observed a higher cyclin E expression in samples of ZAP-70 positive patients, which may reflect a larger proliferating compartment in vivo compared to ZAP 70 negative patients. In our opinion, high CD71 expression may represent both increased cell proliferation and cellular activation in CLL.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, we found that bcl2-CD71-subset was significantly correlated with lower ZAP-70 (p ¼ 0.001), thus hypothesizing a reduced proliferation and higher apoptosis within ZAP-70 negative CLL subset. On this line, Bogner et al [46] observed a higher cyclin E expression in samples of ZAP-70 positive patients, which may reflect a larger proliferating compartment in vivo compared to ZAP 70 negative patients. In our opinion, high CD71 expression may represent both increased cell proliferation and cellular activation in CLL.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the fact that MCL-1 expression is not different in ZAP 70-positive (aggressive) vs. ZAP 70-negative (indolent) B-CLL cells (37), it represents a relevant therapeutic target in both acute and chronic lymphoid malignancies, because its silencing is sufficient to promote apoptosis in ALL and CLL cells and increase sensitivity to rituximab-mediated apoptosis (38). Interestingly, miR-29b has also been identified to target Mcl1 in a cholangiocarcinoma model (39), and many pieces of evidence converge in defining a role of the miR-29 family as TSGs in both solid (40) and hematologic malignancies (41).…”
Section: Variation Of Expression Of Mir-15a/mir 16-1 Targets In Primamentioning
confidence: 99%
“…As expected, no difference was observed before and after treatment with more than 98% of cells in the G0 phase of the cell cycle in every sample tested (data not shown). We have reported previously that cyclin E is strongly expressed in B-CLL cells and is downregulated upon mTOR inhibition [7,20,22]. In addition, the cell cycle inhibitor p27 is also strongly expressed in B-CLL cells and is also regulated in part by mTOR [23,24].…”
Section: Correlative Studiesmentioning
confidence: 99%
“…Mabs specific for p27 (clone G173-524) were purchased from Pharmingen (San Diego, CA, USA). Analysis of ZAP-70 expression was performed with appropriate positive and negative controls as published previously [20] using a ZAP-70 antibody (clone 29) from BD Transduction Laboratory, Mississauga, Canada.…”
Section: Correlative Laboratory Studiesmentioning
confidence: 99%